Inscription referring to the shrine of Gokarna Deva - Temples of India Project Team (Jio Institute, 2024)
The Bisaldeo Temple is referred to as the shrine of Gokarna Deva in its inscriptions. An inscription on a left-hand pillar in the vestibule of the temple, dated 1187 CE (1244 VS), during the reign of Prithviraj Chauhan, refers to the hall of this temple as Shri Gokarna mandapa. Carlleyle had highlighted two more short inscriptions from 1174 CE and 1187 CE (1231 VS and 1244 VS, respectively) on the same pillar and on the left side of the entrance of the temple, which also refers to Shri Gokarna.